The Effectiveness of Acupressure Therapy and Increasing Knowledge of Hypertension Diet in Anjir Serapat Village Muara 1 - S, Evita; Gusdiandi, Hendy; Amalia, Khalisah; Mira, Mira; Ihsan, Radifan (UrbanGreen Central Media, 2025)
Hypertension is a common health problem and is known as the